2011
DOI: 10.1111/j.1748-0361.2010.00356.x
|View full text |Cite
|
Sign up to set email alerts
|

To Give or Not to Give: Approaches to Early Childhood Immunization Delivery in Oregon Rural Primary Care Practices

Abstract: Context-Little is known about rural clinicians' perspectives regarding early childhood immunization delivery, their adherence to recommended best immunization practices, or the specific barriers they confront.Purpose-To examine immunization practices, beliefs, and barriers among rural primary care clinicians for children in Oregon and compare those who deliver all recommended immunizations in their practices with those who do not.Methods-A mailed questionnaire sent to all physicians, nurse practitioners, and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
31
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(34 citation statements)
references
References 21 publications
2
31
0
1
Order By: Relevance
“…Recommendation behavior differed by specialties. Pediatricians were more likely to recommend or offer vaccines [ 118 ] (AOR = 2.55) [ 52 ] than OBGYNs (AOR = 0.5) [ 101 ], family physicians (FP) (A/OR = 2.0–3.49) [ 46 , 47 , 84 , 116 , 127 , 129 ], and GP [ 46 , 47 , 118 ]. Pediatricians placed greater importance than FPs on guidelines (67% vs. 44%, OR = 2.6) and parental requests (61% vs. 45%, OR = 1.9) regarding varicella vaccine [ 84 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recommendation behavior differed by specialties. Pediatricians were more likely to recommend or offer vaccines [ 118 ] (AOR = 2.55) [ 52 ] than OBGYNs (AOR = 0.5) [ 101 ], family physicians (FP) (A/OR = 2.0–3.49) [ 46 , 47 , 84 , 116 , 127 , 129 ], and GP [ 46 , 47 , 118 ]. Pediatricians placed greater importance than FPs on guidelines (67% vs. 44%, OR = 2.6) and parental requests (61% vs. 45%, OR = 1.9) regarding varicella vaccine [ 84 ].…”
Section: Resultsmentioning
confidence: 99%
“…Believing vaccines would be accepted by vaccinators [ 74 ] (OR = 6.41) [ 92 ], vaccine providers (OR = 6.65) [ 39 ], and other professionals (OR = 7.39) [ 57 ] had positive associations. Reported barriers included lack of time [ 63 , 67 , 78 , 82 , 83 , 94 ], logistical difficulties [ 45 , 48 , 63 , 67 , 68 , 95 , 116 ] such as storage [ 85 ], and failure to discuss the vaccine during visits [ 117 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have demonstrated persistent disparities in rural settings compared to urban areas in general health care access ( Douthit et al, 2015 ) and mortality ( Moy et al, 2017 ) indicating unique challenges to accessing medical care and preventive health services in rural communities. Although studies have demonstrated rural versus urban differences in variation in immunization delivery ( Fagnan et al, 2011 , O'Leary et al, 2015 ), explanations specific to why rural children are undervaccinated remains understudied.…”
Section: Introductionmentioning
confidence: 99%
“…One major area where vaccine wastage occurs is during childhood immunizations, which is conpounded by the challenge of incorporating new vaccines into the already crowded immunization schedule adopted by the U.S. governement. In addition, an increasing numbers of health providers and parents are opposed to add immunization requirements, which prevents an efficient resource management [6][7][8].…”
Section: Introductionmentioning
confidence: 99%